A juvenile climbing exercise establishes a muscle memory boosting the effects of exercise in adult rats. (20th September 2022) - Eftestøl, Einar; Ochi, Eisuke; Juvkam, Inga S.; Hansson, Kenth‐Arne; Gundersen, Kristian
Abstract: Aim: Investigate whether juvenile exercise could induce a long‐term muscle memory, boosting the effects of exercise in adults. Methods: We devised a 5‐week climbing exercise scheme with food reward administered to male juvenile rats (post‐natal week 4–9). Subsequently, the animals were subjected to 10 weeks of detraining (week 9–19) without climbing and finally retraining during week 19–21. Results: The juvenile exercise increased fiber cross‐sectional area (fCSA) by 21% ( p  = 0.0035), boosted nuclear accretion by 13% ( p  = 0.057), and reduced intraperitoneal fat content by 28% ( p  = 0.007) and body weight by 9% ( p  = 0.001). During detraining, the fCSA became similar in the animals that had been climbing compared to naive controls, but the elevated number of myonuclei induced by the climbing were maintained (15%, p  = 0.033). When the naive rats were subjected to 2 weeks of adult exercise there was little effect on fCSA, while the previously trained rats displayed an increase of 19% ( p  = 0.0007). Similarly, when the rats were subjected to unilateral surgical overload in lieu of the adult climbing exercise, the increase in fCSA was 20% ( p  = 0.0039) in the climbing group, while there was no significant increase in naive rats when comparing to the contralateral leg. Conclusion: This demonstrates that juvenile exercise can establish a muscle memory boosting the effects of adult exercise. The juvenile climbing exercise with food reward also led to leaner animals with lower body weight. These differences were to some extent maintained throughout the adult detraining period in spite of all animals being fed ad libitum, indicating a form of body weight memory.